Toxopathological and Cytogenetic Effects of Commercial Sweetener Aspartame after Chronic Oral Administration in Rat Pups (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: This study was done to evaluate the potential toxic effect of aspartame (APS) artificial sweetenerafter chronic oral administration in rat pups as a model for children that consumption high quantities ofdifferent types of sweets and juices from the peddler, regularly and daily.Methods: Twenty-four rat pups were divided equally into three groups. Therapeutic dose group (T1) anddouble dose group(T2) received 0.08, 0.16 g/kg. body weight(BW), respectively, while control group (C)received distilled water orally for 90 (d)days.Results: The result of present study revealed that there was an increased consumption of food, water andarising nervous signs(aggressive) in T1 and T2 groups comparing with control. The cytogenetic studyincludes the mitotic index and blast index showing a substantial decline relative to the control one inboth treated groups. While the blast index showed a significant reduction(P<0.05) in T2 relative to T1and the control group. No chromosomal aberration observed in all groups exposed to aspartame. Differenthistopathological lesions were recorded in the liver of T1 group represented by inflammatory cell (neutrophil& mononuclear cell) aggregation around the blood vessels. While noted in a double dose group (0.16g/kg.bw), a granulomatous lesion with mild change in fat is shown.Conclusion: Used daily for lengthy periods ASP has cytogenetic and pathological risks.